2017
DOI: 10.16965/ijar.2016.367
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry and Surgical Importance of Foramen Magnum

Abstract: Introduction:The Foramen Magnum (FM) lies in an anteromedian position and leads into the posterior cranial fossa. It is oval and wider behind, with its greatest diameter being anteroposterior. It contains the lower end of the medulla oblongata, meninges, vertebral arteries and spinal accessory nerve. The apical ligament of dens and the tectorial membrane pass through it, to attach to the basiocciput. Anteriorly the margin of foramen magnum is slightly overlapped by the occipital condyles. Transcondylar, suprac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…21 Konig et al used dimensions of the FM analysis in 3D computer tomography, which reported 81% accuracy in sex determination. 22 Despite the anatomical and clinical significance of the dimensions and different shapes of FM in determining the age and sex of individuals, there is still no fundamental study. It should be noted that the determination of age and sex by FM varies in different populations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21 Konig et al used dimensions of the FM analysis in 3D computer tomography, which reported 81% accuracy in sex determination. 22 Despite the anatomical and clinical significance of the dimensions and different shapes of FM in determining the age and sex of individuals, there is still no fundamental study. It should be noted that the determination of age and sex by FM varies in different populations.…”
mentioning
confidence: 99%
“…They also stated that the relationship between age and FM region variables is not completely accurate 21 . Konig et al used dimensions of the FM analysis in 3D computer tomography, which reported 81% accuracy in sex determination 22 . Despite the anatomical and clinical significance of the dimensions and different shapes of FM in determining the age and sex of individuals, there is still no fundamental study.…”
mentioning
confidence: 99%
“…In an ovoid type of the FM, for example, the surgeon may find it difficult to explore the anterior portion of the FM. 19 The shape of the FM can also be determined by using the FMI. Muthukumar et al have considered the FM to be oval when the FMI was > 1.2, and they considered the rest (FMI < 1.2) as round.…”
Section: Discussionmentioning
confidence: 99%